Innovation in difficult times - Arbix, Glauco; Miranda, Zil (Plural, 2015)
Low productivity is at the basis of Brazilian economy difficulties and in its capacity of supporting long cycles of growth and quality jobs creation. Stagnant since the 1970s, the economic agenda has a central point: how do to overcome the low structural performance of Brazilian economy? Infrastructure, tax system, low degree of competition and an inappropriate regulatory system rise as items of first importance. However, only the increase of workers’ skills will enable the integration of people, ideas, technologies, processes and more advanced production models. Thus giving knowledge the capacity to move economy’s mechanisms. Such a process is called innovation. And the capacity of uninterruptedly incorporating, adapting and producing innovation is key to facilitate increased efficiency results in economic activities. This is what economy most urgently needs. It is the focus item in the agenda that will connect Brazil to the future